NP-003 Steady-state pharmacokinetics and early safety data in HIV-infected african children weighing ≥25 kg after switching to 50 mg film-coated dolutegravir tablets in the ODYSSEY trial. (24th March 2020) - Bollen, PDJ; Turkova, A; Kaudha, E; Chidziva, E; Lugemwa, A; Kekitiinwa, A; Parker, A; Shakeshaft, C; Montero, S; Colbers, A; Nanduudu, A; Mujuru, H; et al.
Abstract : Background and importance: ODYSSEY is an ongoing international randomised trial evaluating dolutegravir (DTG)-based antiretroviral therapy (ART) versus standard-of-care in HIV-infected children starting first- or second-line ART. Pediatric DTG film-coated tablets (FCTs) of 10 mg and 25 mg are unavailable in low- and middle income countries (LMIC) were most HIV-infected children live. Adult DTG 50mg FTCs are produced by generic manufacturers at low-cost, are well-tolerated, and already available in many high- and LMICs. Aim and objectives: Within ODYSSEY pharmacokinetic (PK) substudies were undertaken to assess PK and safety data for a simplified paediatric DTG dosing approach using WHO weight bands (WBs) 25 to <30 kg and 30 to <40 kg and once daily 50 mg adult DTG doses. Materials and methods: Steady-state 24-hour PK curves were constructed from data in children (≥3 h fasted) observed taking current EMA-approved DTG doses of 25 mg and 35 mg (10 mg+25 mg FCTs)) in 25-<30 kg and 30-<40 kg WBs, respectively. After all children switched to single daily 50 mg DTG tablet, a second 24 h PK curve was constructed. We aimed to achieve DTG exposures comparable to historical adult data for DTG 50 mg FCTs QD taken under fasted conditions (geometric mean (GM): Ctrough 0.83 mg/L, AUC0-24h 43.4 h*mg/L, Cmax 3.34 mg/L). Additionally, results were compared to PK data for DTG 50mg BID in adults (GM ranges: Ctrough 2.41 to 2.72 mg/L, AUC0-24h 93.4 to 92.7 h*mg/L, Cmax 5.41 to 5.55 mg/L). Safety was evaluated after switch to the 50mg dose at 2, 4 and 12 weeks and then every 12 weeks. Results: 28 black-African children (52 PK profiles) from Uganda and Zimbabwe (61% male) with a median (range) age of 11.0(7.5–17.9) years old were included. For children weighing 25-<30 kg on DTG 25 mg (17 profiles) GM with coefficient of variation (CV%) for Ctrough and AUC0-24h was 0.39(48) mg/L and 33.1(23) h*mg/L, respectively, and after switch to DTG 50 mg (16 profiles) values were 0.77(43) mg/L and 58.6(28) h*mg/L, respectively. For children weighing 30-<40 kg on DTG 35 mg (9 profiles), Ctrough and AUC0-24h were 0.46(63) mg/L and 40.3(35) h*mg/L, and after switch to DTG 50 mg (10 profiles) values 0.63(49) mg/L and 53.5(32) h*mg/L, respectively. The 50 mg dose resulted in Cmax values of 5.41(25) mg/L and 5.22(25) mg/L in WB 25-<30 kg and 30-<40 kg, respectively, which did not exceed historical Cmax values for adults on 50 mg BID. After a median (IQR) follow-up of 30(12–30) weeks on 50 mg DTG 3/28(11%) children had grade 3 or 4 adverse events (one SAE; cryptococcal meningitis) and all were considered unrelated to DTG. Conclusions and relevance: Adult 50 mg FCT once-daily dolutegravir provides appropriate PK profiles in children ≥25 kg, with no safety signal, allowing practical dosing and rapid access to dolutegravir. WHO has released new pediatric dosing guidelines in response to these results.